Lab-on-PCB Devices - Perdigones, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Lab-on-PCB devices can be considered an emerging technology. In fact, most of the contributions have been published during the last 5 years. It is mainly focussed on both biomedical and electronic applications. The book includes an interesting guide for using the different layers of the Printed Circuit Boards for developing new devices; guidelines for fabricating PCB-based electrochemical biosensors, and an overview of fluid manipulation devices fabricated using Printed Circuit Boards. In addition, current PCB-based devices are reported, and studies for several aspects of research and development of lab-on-PCB devices are described.